Plan de revitalización cultural de los bienes inmateriales de la comunidad de Oyacachi, cantón el Chaco, provincia Napo - Novoa Catucuamba, Nancy Valeria (2015)
The research was conducted in” Oyacachi” Kichwa community. It is located in Chaco Canton, Napo Province. The problem was the cultural identity loss. This proposal is based on cultural revitalization plan´s design, by applying collective memories, participatory workshops, interviews, surveys and data sheets CPI (INPC). Also, different research types were used as primary and secondary sources. These factors helped it. It has three chapters. At the first chapter, a situational analysis was conducted in order to identify the current situation in social, economic, political, environmental and cultural in community characteristics. At the second chapter, an intangible cultural property inventory was developed. Here, the categories and cultural areas identified through the CPI data sheets application. Also, surveys were applied to know the historical and cultural heritage of Oyacachi people, through the population selection and segmentation by age. At the third chapter, the cultural revitalization plan was developed. For this three and five sub- protection, rescue and dissemination programs of craftsmanship, constructive knowledge, ancestral knowledge, arts and community practices was developed. All these actions contribute to the objectives of Good Living at “Oyacachi” Kichwa community.